2019
DOI: 10.3390/genes10060431
|View full text |Cite
|
Sign up to set email alerts
|

Single Fragment or Bulk Soil DNA Metabarcoding: Which is Better for Characterizing Biological Taxa Found in Surface Soils for Sample Separation?

Abstract: In forensic geology casework, sample size typically limits routine characterization of material using bulk approaches. To address this, DNA-based characterization of biological taxa has received attention, as the taxa present can be useful for sample-to-sample comparisons and source attribution. In our initial work, low biodiversity was captured when DNA barcodes were Sanger-sequenced from plant and insect fragments isolated from 10 forensic-type surface soils. Considering some forensic laboratories now have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(104 reference statements)
1
3
0
Order By: Relevance
“…Inability to detect this species in some replicates might be due to the effects of PCR and variation in the soil material used for DNA extractions. Similar results have been previously published and thus sensitivity and reproducibility of the eDNA metabarcoding results have been a challenging issue ( Boggs, Scheible & Meiklejohn, 2019 ). To avoid replicate variation, it has been suggested that performing technical replicates during PCR and pooling them before downstream processing could be effective ( Lauber et al, 2013 ; Young, Weyrich & Cooper, 2016 ; Demanèche et al, 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…Inability to detect this species in some replicates might be due to the effects of PCR and variation in the soil material used for DNA extractions. Similar results have been previously published and thus sensitivity and reproducibility of the eDNA metabarcoding results have been a challenging issue ( Boggs, Scheible & Meiklejohn, 2019 ). To avoid replicate variation, it has been suggested that performing technical replicates during PCR and pooling them before downstream processing could be effective ( Lauber et al, 2013 ; Young, Weyrich & Cooper, 2016 ; Demanèche et al, 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…Raw sequence data was processed and analyzed following the pipeline described in [20]. Briefly, raw reads were filtered and trimmed using the default parameters of the DADA2 pipeline [21].…”
Section: Sequence Data Analysismentioning
confidence: 99%
“…DNA metabarcoding is an approach that allows for the amplification of small, yet, informative regions of the genome to characterize biological communities. Research assessing the bacterial [14,15], plant [14,16,17], insect [16,17], fungal [17,18], and eukaryotic [14,17] communities within mock soil core evidence has highlighted promising outcomes for use in forensic geology casework. Other studies have incorporated realistic crime scene scenarios by including mock evidence in their characterization of the bacterial [19,20] and eukaryotic [21] communities.…”
Section: Introductionmentioning
confidence: 99%